STABILITY OF RAPESEED (Brassica napus L. ) VARIETIES UNDER RAINFALL CONDITIONS IN NORTHEREN OF IRAQ - Mohammed Y. Hammed (Mesopotamia Journal of Agriculture)
Four rapeseed varieties, Paktol, Kebel, Forte and Karat were tested in five environments represented limited and semi-limited dryland area in northern of Iraq, Mosul province (Rashidia during 1999-2000 and 2000-2001, singar during 2000-2001 and Bashiqa site during 2000-2001 and 2001-2002 seasons) in order to determine stability of these varieties for plant height, heading,yield and its components.Significant varietal and environments differences were observed for the traits investigated except no. of seed per pod and 1000 seed weight.GXE interaction effect was highly significant for all traits except 1000 seed weight. Paktol were better adapted to favorite environments for plant height, no. of days to heading and no. of pods per plant and better adapted to a wide of environments and stable for seed yield.